Experimental study and Ab-initio calculations on the molecular structure, infrared and Raman spectral properties of dinitroimidazoles - Ravi, P. (Chemical Data Collections, 2017)
The structural and vibrational properties of 1,4-dinitroimidazole, 2,4-dinitroimidazole and 1-methyl-2,4-dinitroimidazole have been explored both experimentally and theoretically. The N1-N6, C2-NO2, C4-NO2, N1-CH3 lengths were found to be varied with the levels of theory and the calculated values were over estimated compared with those of experimental values. The experimental vibrational frequencies were compared with those values calculated at the HF/6–311 ++G(d,p), B3P86/6–311 ++G(d,p), B3LYP/6–311 ++G(d,p) and B3LYP/aug-cc-pVDZ levels. The calculated frequencies were in good agreement with the experimental values and the relative mean deviations between the measured and calculated vibrational frequencies were smaller than 1% for all molecules. The discrepancies in the bond lengths bond angles and harmonic frequencies are confined to the relative positions of NO2 groups that present a great deviation from the planarity of the molecule. Nevertheless the structural parameters and harmonic vibrational frequencies of nitroimidazoles calculated at the B3LYP/aug-cc-pVDZ level are superior compared with those values computed from other levels of calculation.